The Significance of Autonomous Learning Skills in the Process of Language Acquisition (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article aims to explore the significance of autonomous learning in language acquisition, examining its impact on learner motivation, engagement, and overall proficiency. Besides that, the benefits, challenges and effective strategies of autonomous learning are also analyzed.